Case report: A five−case series of 18−month home use of a conversational companion robot for psychological support in older people with mild cognitive impairment or late−onset psychosis - Nagata, Yuma; Satake, Yuto; Yamazaki, Ryuji; Nishio, Shuichi; Ishiguro, Hiroshi; Ikeda, Manabu (Frontiers in Psychiatry, 2026)
Although companion robots have demonstrated psychological benefits for older adults, most studies have focused on short-term use or institutional settings. This case series with integrated qualitative analysis describes five cases involving the long-term use of a conversational companion robot (RoBoHoN, Sharp) among community-dwelling women aged 85 to 90 with mild cognitive impairment or late-onset psychosis. After an initial exploratory phase (2–5 months) and a 2-month washout, the robot was installed in each home for 18 months. All participants operated the robot in daily life, with only intermittent light−touch support from caregivers or the team when needed. Usability assessments showed high satisfaction and ease of use. Although standardised psychological scales showed no consistent improvements, participants reported enjoying conversations with the robot. Four of the five expressed a desire to continue using the robot after the study. These findings support the feasibility and potential long-term acceptability of companion robots among cognitively challenged older adults living at home. The case series suggests such robots may foster sustained engagement even in vulnerable populations. Further studies with larger samples are needed to evaluate the psychological effects of long-term companion robot use in home settings.